Basics of Calculating Anti-Theft Crane Device from Eccentric and Tick-Borne Mechanisms - N. M. Selivonchik; N. L. Nesterenko (Наука и техника)
According to the requirements of the “Rules for industrial safety of cranes”, anti-theft devices must ensure that cranes under the influence of wind force stop at any point on the track, including at the junction of rails connected by side strips. Various types of anti-theft crane devices recommended for use have a number of disadvantages. Thus, the supply  of anti-theft crane devices made in the form of lever grips interacting with the rail head with mechanisms for disengaging  and converging grippers with electromechanical, electromagnetic, hydraulic or pneumatic drives complicates their design. There are also known anti-theft crane devices, in which the stopping of cranes on a rail track is carried out by a locking eccentric interacting with the surface of the rail head. The reliability of such devices is insufficient, since, due to the constant force of the spring, the adhesion force of the eccentric to the rail does not depend on the changing wind force. The paper proposes the basics of calculating the anti-theft crane device, representing the kinematic connection of two mechanisms – eccentric and thick-borne, which allows to solve a number of the above problems.